Influence of Phytogenic Feed Additive on Performance of Feedlot Cattle - Piran Filho, Francisco Antonio; Turner, Tyler Dustin; Mueller, Isabel; Daniel, Joao Luiz Pratti (Frontiers in Animal Science, 2021)
This study evaluated the influence of a blended phytogenic feed additive on feed intake, feeding behavior, nutrient digestibility, and growth performance during feedlot adaptation, early and late finishing periods as well as carcass traits. Twenty-six crossbred F1 Angus × Nellore bulls (19 mo ± 4 d) were housed in individually pens and fed a high-forage receiving diet for 7 days. At the end of the receiving period, bulls were weighted (initial shrunk body weight (SBW) 363 kg ± 20 kg), blocked by SBW and randomly assigned to two treatments; Control: without any additive or PHY: 150 ppm of a phytogenic feed additive fed throughout the adaptation and finishing phases. Bulls were transitioned through four steps over 18 days to a high-grain finishing diet (as % DM, 64% rehydrated corn grain silage, 19% corn gluten feed, 13% sugar cane bagasse and 4% minerals, urea and vitamins mix). The finishing phase lasted 68 days, with mid-point measurements dividing early and late finishing period. The PHY group DMI was greater during adaptation and late finishing periods (P < 0.05), with a tendency during early finishing period (P = 0.06). Number of daily meals was similar between treatments (P = 0.52), but an increased meal length was noted for PHY group (P < 0.05, which contributed to their greater DMI. Diet digestibility remained similar between groups during the finishing periods (P > 0.1). Ruminitis scores were low and liver abscess similar between treatments. Final SBW tended to be higher (P = 0.09) and hot carcass weight was greater for the PHY group (P < 0.05), with no differences on dressing percentage, ribeye area and marbling score. In conclusion, the PHY treatment had positive effects on intake and carcass weight, without increasing metabolic disorders.